Monitoring of natural reproduction of fish populations of Edilsor Lake - Sergaliyev, N.Kh.; Kakishev, M.G.; Sultanov, E.S.; Sarmanov, A.E.; Bakiyev, S.S. (Fundamental and Experimental Biology, 2022)
The article presents the results of monitoring the commercial fish populations of Edilsor Lake. Edilsor is one of the large lakes of the West Kazakhstan region of fishery importance, in connection with which the moni-toring of the natural numbers of populations of aboriginal commercial fish species of the studied reservoir is relevant. Control catches were used to analyze the state of natural fish populations. As tools for catching bio-logical objects, commercial fish, lake plug-in nets with mesh sizes of 30–70 mm were used. Control catches of aboriginal commercial fish were carried out during the period of field studies. The captured biological ob-jects were subjected to the analysis of such biological indicators as species, age composition, ratio of females and males in the catch, weight, length of the whole body of fish, according to the results obtained, the average values were determined. As a result of control catches, the species composition of the ichthyofauna of Lake Edilsor included the following species of aboriginal commercial fish: carp — 7.1 %, bream — 16.7 %, blue bream — 7.1 %, crucian carp — 4.8 %, perch — 64.3 %. The largest population was characterized by the perch population, which amounted to 27 individuals, the bream was less common — 7 individuals, the carp and blue bream — 3 individuals, the smallest number was observed in the population of crucian carp, which amounted to 2 individuals. According to the weight ratio, fish species are located as follows: perch — 40 %, carp — 32.5 %, bream — 15.8 %, crucian carp — 8.5 %, blue bream — 3.2 %. The largest mass falls on rep-resentatives of perch — 6.94 kg, followed by carp — 5.63 kg, bream — 2.73 kg, crucian carp — 1.47 kg, blue bream — 0.56 kg.